Response of diverse wheat genotypes to moringa leaf extract concentrations and nitrogen levels on agronomic performance and nitrogen use efficiency under arid conditions - Agwa, Eman Y.; Shormillesy, Salwa M.A.I. Ash-; Gomaa, Mohamed A.; El Sanatawy, AbdAllah M. (International Journal of Aquatic Research and Environmental Studies, 2026)
Sustainable agricultural practices are crucial for enhancing crop production in arid regions. Improving growth performance and nitrogen use efficiency of wheat genotypes contributes to yield stability in challenging environments. This study investigated the effects of foliar application of moringa leaf extract (MLE) at different concentrations (0%, 3%, and 6%) and varied N fertilizer levels (142, 190, and 238 kg N/ha) on growth, yield, and NUE of three diverse wheat cultivars (Sids 14, Sakha 95, and Giza 171) under field conditions in an arid environment over two growing seasons.  The experimental site soil was clay and the climate was dry with low precipitation. The results indicated that increasing MLE concentration and N level significantly improved all studied growth, yield, and quality traits. In particular, the application of MLE in concentration 6% resulted in the highest grain yield (6871 and 6888 kg/ha) and straw yield (9368 and 9310 kg/ha), representing significant increases over the untreated control in both seasons. For quality, 6% MLE improved grain N content (up to 15.09 mg/g), straw N content (up to 7.67 mg/g), and grain N uptake (up to 104.66 kg/ha), with NUE peaking at 28.53 kg/kg. High N application (238 kg N/ha) also produced a significant yield increment by increasing grain yield compared to the lowest N level (142 kg N/ha). Cultivars Sids 14 and Giza 171 surpassed Sakha 95 in most yield and N accumulation parameters. Principal component and hierarchical cluster analyses confirmed that combinations of 6% MLE and 238 kg N/ha, especially with Sids 14 and Giza 171, maximized yield and NUE traits. Certain cultivars such Sids 14 and Giza 171 are more appropriate for these practices under arid clay soil conditions. Therefore, foliar application of 6% MLE combined with 238 kg N/ha with appropriate cultivars could significantly enhance wheat yield, quality, and NUE for improving wheat productivity in arid environments.
Keywords: Genotypic variations, foliar biostimulants, nitrogen use efficiency, plant nutrition, sustainable wheat production, crop management, plant growth regulators, principal component analysis, hierarchical clustering heatmap